A Readily Scalable, Clinically Demonstrated, Antibiofouling Zwitterionic Surface Treatment for Implantable Medical Devices. Issue 20 (11th April 2022) - McVerry, Brian; Polasko, Alexandra; Rao, Ethan; Haghniaz, Reihaneh; Chen, Dayong; He, Na; Ramos, Pia; Hayashi, Joel; Curson, Paige; Wu, Chueh‐Yu; Bandaru, Praveen; Anderson, Mackenzie; et al.
Abstract: Unlike growth on tissue, microbes can grow freely on implantable devices with minimal immune system intervention and often form resilient biofilms that continuously pump out pathogenic cells. The efficacy of antibiotics used to treat infection is declining due to increased rates of pathogenic resistance. A simple, one‐step zwitterionic surface modification is developed to significantly reduce protein and microbial adhesion to synthetic materials and demonstrate the successful modification of several clinically relevant materials, including recalcitrant materials such as elastomeric polydimethylsiloxane. The treated surfaces exhibit robust adhesion resistance against proteins and microorganisms in both static and flow conditions. Furthermore, the surface treatment prevents the adhesion of mammalian fibroblast cells while displaying no cytotoxicity. To demonstrate the clinical efficacy of the novel technology in the real‐world, a surface‐treated, commercial silicone foley catheter is developed that is cleared for use by the U.S. Food and Drug Administration (K192034). 16 long‐term catheterized patients received surface‐treated catheters and completed a Patient Global Impression of Improvement (PGI‐I) questionnaire. 10 out of 16 patients described their urinary tract condition post implantation as "much better" or "very much better" and 72% ( n  = 13) of patients desire to continue using the surface‐treated catheter over conventional latex or silicone catheters. Abstract : A simple process has been developed to treat the surfaces of implantable medical devices with zwitterionic materials to reduce hospital acquired infection and complications. The process meets the regulatory and scalability requirements to treat real‐world devices. Long‐term catheterized patients who replaced conventional catheters with surface‐treated catheters report improved urinary tract condition and quality of life.